Abdominal wall desmoid tumors associated with pregnancy: current concepts. Issue 11 (November 2009) - Johner, Amanda; Tiwari, Pari; Zetler, Peter; Wiseman, Sam M
The desmoid tumors (DTs) are unusual soft-tissue tumors that have a propensity for aggressive local growth and may develop during, or soon after pregnancy. Pregnancy-associated DTs are uncommon and optimal management of this tumor has yet to be defined. Currently, controversy centers on the timing of surgical resection and is influenced by the potential for tumor growth and the effects of a gravid uterus. A review of current literature in which DTs were managed either during pregnancy or in the postpartum period, was carried out. Surgical resection of these tumors has been performed successfully both during and soon after delivery, and the role of postpartum radiotherapy, chemotherapy and other medical intervention remains controversial. Management of DTs diagnosed during pregnancy is complex and treatment must be individualized.